Complexos de Ru e Pd com bases de Schiff de ditiocarbazatos com interesse bioinorgânico e quimioterápico - Graminha, Angelica Ellen (2010)
The present work reports the synthesis of dithiocarbazate Schiff s bases, which are versatile ligands with a significant interest due to both property and biological application. The focus of this study was the synthesis of bidentate, tridentate and tetradentate Schiff s bases derived from acetophenone, 2-acetylpyridine, benzylacetylacetone and 2,6-diacetylpyridine with S-benzyl and S-pnitrobenzyldithiocarbazate. Such ligands have been characterized through melting point, vibrational absorption spectroscopy in infrared region, elemental analysis, RMN 1H, gCosy gHSQC and gHMBC and electrochemical studies. The crystallographic structure of the ligand S-benzyl-N-(acetophenone)dithiocarbazate (AcFBz) was given. During the characterization of the ligands S-benzyl- (FACACBz) and S-p-nitrobenzyl-N- (benzyacetone)dithiocarbazate(FACACBzNO2 ) the formation of a cyclic ligand, which keeps the molecular formula of the originally proposed structure, was found. From the ligands derived from benzylacetone (FACACBz and FACACBzNO2), 2-acetylpyridine (AcpyBz and AcpyBzNO2) and 2,6-diacetylpyridine (DAPBz e DAPBzNO2), palladium (II) complexes( [Pd(FACACR)PPh3], [Pd(AcpyR)PPh3]PF6 and [Pd(DAPR)] ) have been synthesized with R= Bz or BzNO2. These compounds have been characterized through several techniques and the structure of the complexes [Pd(FACACBz)(PPh3)] and [Pd(FACACBzNO2)(PPh3)] was given. The electrochemical studies of the complexes [Pd(FACACR)PPh3] and [Pd(AcpyR)PPh3]PF6 (R= Bz ou BzNO2) showed distinct electrochemical behavior. Both complexes [Pd(FACACR)PPh3] and [Pd(AcpyR)PPh3]PF6 contain irreversible potential, while the [Pd(FACACR)PPh3] complexes are oxidized by PdII/PdIII and the [Pd(AcpyR)PPh3]PF6 complexes show reduction potential of PdII/PdI. Furthermore, complexes of ruthenium (II) with ligands derived from both 2-acetylpyridine (AcpyBz, AcpyBzNO2) and acetophenone (AcFBz and AcFBzNO2) with different precursors, such as [RuCl2(PPh3)3] and [RuCl2(dpbp)(PPh3)], have been studied. All ruthenium complexes are neutral, because the ligands are anionic due to the deprotonation of one of the nitrogen from the chain. Thus, the ruthenium compounds with bidentate ligand AcFBz and AcFBzNO2 present a xvii general formula [Ru(L)2(PPh3)2] and [Ru(L)2(dppb)], while the tridentate ligands AcpyBz and AcpyBzNO2 form [RuCl(L)(PPh3)2] and [RuCl(L)(dppb)] complexes. The crystallographic structure of the complex [RuCl(AcpyBz)(dppb)] was given. Ruthenium (II) complexes have also been synthesized through Schiff s bases derived from 2,6- diacetylpyridine DAPBz and DAPBzNO2.These compounds, as well as the respective palladium complexes, showed low solubility restricting the use of some techniques in order to characterize them. Cytotoxicity assays of both compounds and their respective ligands have been carried out on cell lines K562 (leukemia myeloid akut), S180 (Murine ascitic Sarcoma) and MDA-MB231 (breast cancer), except the Pd and Ru compounds containing the DAPBz e DAPBzNO2 ligands, due to their low solubility. Cellular viability assays have been carried out in order to ascertain the cytotoxicity of both complexes and their ligands in vitro. In some cases the complexibility improved the activity whereas it has generated selectivity to the complexes in others.